Epoxy resin anti-collision, anti-corrosion and wear-resistant material and preparation method thereof

By using graphene oxide and modified zirconia as fillers in epoxy resin materials, the problem of insufficient wear resistance of existing epoxy resin materials is solved, and the corrosion and mechanical properties of the material are improved, and the service life is extended.

CN119331486BActive Publication Date: 2025-03-11YANTAI HAIYU NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411896642.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

During the use of existing epoxy resin materials, their wear resistance needs to be further improved.

Method used

By preparing an epoxy resin anti-collision-resistant wear-resistant material, graphene oxide and modified zirconia are used as wear-resistant fillers and anti-corrosion fillers, respectively, and a dense material structure is formed by sonication and chemical reaction methods, combining diluents, defoaming agents and toughening agents.

Benefits of technology

It improves the corrosion resistance and mechanical properties of epoxy resin materials, significantly improves its toughness and wear resistance, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331486B_ABST
    Figure CN119331486B_ABST
Patent Text Reader

Abstract

The invention discloses an epoxy resin anti-collision, anti-corrosion and wear-resistant material and a preparation method thereof, and the invention relates to the technical field of epoxy resin materials, comprising the following components in parts by weight: 2.5-4 parts of anti-corrosion filler, 1.8-2.5 parts of wear-resistant filler, 25-30 parts of epoxy resin, 10-15 parts of diluent, 1.5-2 parts of defoamer, and 1.5-2 parts of toughening agent; the diluent is a mixed solution of xylene and n-butanol in a volume ratio of 1:2. The epoxy resin anti-collision, anti-corrosion and wear-resistant material and a preparation method thereof, because graphene oxide itself has a two-dimensional flaky structure, bears a certain load in the epoxy resin matrix, disperses stress, and at the same time, modified zirconium oxide particles have higher hardness and strength, and the two act synergistically, so that the modified zirconium oxide fills the gap between the graphene oxide sheets, making the internal structure of the material more compact, reducing the penetration channel of corrosive substances, thereby improving the anti-corrosion performance of the epoxy resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of epoxy resin materials, in particular to an epoxy resin anti-collision, anti-corrosion and wear-resistant material and a preparation method thereof. Background Art

[0002] The Chinese patent application with publication number CN107759976A discloses a highly wear-resistant epoxy resin composite material, which is made of the following raw materials in parts by weight: epoxy resin, highly wear-resistant carbon black, activated carbon, polyetheramine, phenyltrichlorosilane, linseed oil, dimethylaminoethyl acrylate, and deionized water. The beneficial effects of the invention are: acid and alkali resistance, aging resistance, high hardness, good compatibility with liquid oxygen, prevention of bacterial reproduction, activated carbon moisture absorption and deodorization, mildew and moisture resistance, and natural and environmentally friendly. However, the wear resistance of the epoxy resin material prepared by the above-mentioned prior art scheme needs to be further improved during use; for this reason, the present invention provides an epoxy resin anti-collision, anti-corrosion and wear-resistant material and a preparation method thereof to solve the above-mentioned problems. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides an epoxy resin anti-collision, anti-corrosion and wear-resistant material and a preparation method thereof, which solves the problems mentioned in the above background technology.

[0004] To achieve the above objectives, the present invention is implemented by the following technical scheme: an epoxy resin anti-collision, anti-corrosion and wear-resistant material, comprising the following components in parts by weight: 2.5-4 parts of anti-corrosion filler, 1.8-2.5 parts of wear-resistant filler, 25-30 parts of epoxy resin, 10-15 parts of diluent, 1.5-2 parts of defoaming agent, and 1.5-2 parts of toughening agent;

[0005] The diluent is a mixed solution of xylene and n-butanol in a volume ratio of 1:2; the defoamer is 2-ethyl acrylate; and the toughening agent is dibutyl phthalate.

[0006] Preferably, the wear-resistant filler is made by mixing graphene oxide and modified zirconium oxide.

[0007] Preferably, the preparation method of the anticorrosive filler is:

[0008] S1. Pour 0.5-0.75 g of NiPS and 18-22 g of zinc acetate dihydrate into 45 mL of deionized water and stir for 10-12 h to obtain solution A.

[0009] S2. Pour 0.35-0.5 g of thiourea into 15 mL of deionized water and stir until the thiourea is completely dissolved to obtain solution B;

[0010] S3, after mixing solution A and solution B, raise the temperature to 150-170°C and react for 3.5-4h;

[0011] S4. After the reaction is completed, cool naturally to room temperature, centrifuge, wash with water, and then place in a drying oven at 55-65°C to dry for 10-14 hours to obtain the anti-corrosion filler.

[0012] Preferably, the preparation method of the NiPS is:

[0013] S11, 0.3-0.5g and specific surface area of ​​280g / m 2 After mixing fumed silica, 2-2.4 g of nickel nitrate hexahydrate and 1.2-1.4 g of urea, add 50-65 mL of 0.02 mol / L nitric acid and stir until completely dissolved;

[0014] S12, under stirring conditions, heating to 85-90°C and reacting for 7-8h;

[0015] S13. After the reaction is completed, cool to room temperature, centrifuge, wash with water, and then place in a drying oven at 50-60°C to dry for 10-12 hours to obtain NiPS.

[0016] Preferably, the preparation method of the wear-resistant filler is:

[0017] (1) After mixing 8-15 mL of graphene oxide and 4-6 mL of modified zirconium oxide, 1.5-4 mL of N,N-dimethylformamide was added and ultrasonic treatment was performed for 15-25 min;

[0018] (2) Heat the oil bath to 65-75°C, react for 25-40 minutes, and then cool to room temperature;

[0019] (3) After standing for 24 hours, pour off the supernatant, wash the precipitate with anhydrous ethanol for 2-3 times, then wash it with deionized water for 3-5 times, and freeze-dry it for 45-65 minutes to obtain the wear-resistant filler.

[0020] Preferably, the preparation process of graphene oxide includes a pre-oxidation process and an oxidation process.

[0021] Preferably, the pre-oxidation process of graphene oxide is specifically as follows: 1.8-3g of graphite powder, 2-2.5g of K 2 S 2 O 8 2-2.5 g of P 2 O 5 Pour into 10-12mL of concentrated sulfuric acid, heat to 75-80℃ in a water bath, and stir to react for 3-4h; then cool to room temperature, add 350-450mL of deionized water, let stand for 24h, pour out the supernatant, wash the precipitate with deionized water 3-5 times, and then dry in a drying oven at 60-70℃.

[0022] Preferably, the oxidation process of the graphene oxide is specifically as follows:

[0023] Ⅰ. Pour 120 mL of concentrated sulfuric acid into the pre-oxidized graphene and stir in an ice water bath at 0-2°C for 25-35 min;

[0024] Ⅱ. At room temperature, slowly add 12-18g of potassium permanganate and stir to react for 65-72h;

[0025] III. Add 220-250 mL of deionized water and stir for 20-30 minutes;

[0026] IV. First add 650-750mL of deionized water, then add 30% H 2 O 2 Solution;

[0027] V. Centrifuge, discard the supernatant, wash the precipitate three times with 10% by volume dilute hydrochloric acid and deionized water, and then dialyze to neutral to obtain graphene oxide.

[0028] Preferably, the preparation method of the modified zirconium oxide is:

[0029] Add 1.5-4 g of 8-aminopyrene-1,3,6-trisulfonic acid trisodium salt and 10-15 g of nano zirconium oxide to 22-28 mL of anhydrous ethanol, stir evenly, and then ultrasonically disperse for 10-15 minutes; under stirring, heat the water bath to 45-50° C., and add deionized water; after natural precipitation for 24 hours, pour out the supernatant, wash with anhydrous ethanol for 3 times, then wash with deionized water for 3-5 times, and freeze-dry to obtain modified zirconium oxide.

[0030] A method for preparing an epoxy resin anti-collision, anti-corrosion and wear-resistant material comprises the following preparation steps:

[0031] Step 1: After the epoxy resin is heated and liquefied, a diluent and a toughening agent are added in sequence and stirred evenly;

[0032] Step 2: Add anti-corrosion filler and wear-resistant filler, and stir to mix evenly;

[0033] Step 3: Add defoaming agent, stir evenly, evacuate, mold, and cure in an oven at 50-70°C for 12-24h to obtain epoxy resin anti-collision, anti-corrosion and wear-resistant material.

[0034] Beneficial Effects

[0035] The present invention provides an epoxy resin anti-collision, anti-corrosion and wear-resistant material and a preparation method thereof. Compared with the prior art, it has the following beneficial effects:

[0036] (1) The epoxy resin anti-collision, anti-corrosion and wear-resistant material and its preparation method. Graphene oxide itself has a two-dimensional flaky structure, bears a certain load in the epoxy resin matrix and disperses stress. At the same time, the modified zirconium oxide particles have high hardness and strength. The two act synergistically, so that the modified zirconium oxide fills the gaps between the graphene oxide sheets, making the internal structure of the material more compact, reducing the penetration channels of corrosive substances, thereby improving the anti-corrosion and mechanical properties of the epoxy resin; graphene oxide can prevent the expansion of cracks, and the modified zirconium oxide can produce pinning and deflection effects on the crack expansion path. The two work together to consume more energy and significantly improve the toughness of the epoxy resin; graphene oxide can play a lubricating role at the friction interface and reduce the friction coefficient. The modified zirconium oxide can withstand partial wear during the friction process. The two act synergistically, which can effectively reduce the wear rate of the epoxy resin during the friction process, improve the wear resistance, and extend the service life of the material.

[0037] (2) The epoxy resin anti-collision, anti-corrosion and wear-resistant material and its preparation method form chemical bonds and physical entanglements with the epoxy resin by adding anti-corrosion fillers, thereby enhancing the interfacial bonding force, thereby preventing the fillers from separating from the epoxy resin matrix and improving the mechanical properties and stability of the material; and the anti-corrosion fillers overlap and stack each other in the epoxy resin to form a maze-like physical barrier network, which hinders the penetration of corrosive media, oxygen and water vapor, and can be filled in the gaps in the network to make the network denser, effectively extending the diffusion path of the corrosive medium and enhancing the anti-corrosion performance of the epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 SEM images of graphene and graphene oxide provided by the present invention;

[0039] Figure 2 The SEM images of the graphene oxide and nano zirconium oxide composite and the graphene oxide and modified zirconium oxide composite provided by the present invention are shown. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In the technical scheme, the preparation method of modified zirconium oxide is as follows: add 1.5 g of 8-aminopyrene-1,3,6-trisulfonic acid trisodium salt and 10 g of nano zirconium oxide to 25 mL of anhydrous ethanol, stir evenly, and ultrasonically disperse for 10 minutes; under stirring conditions, heat the water bath to 45°C and add deionized water; after natural precipitation for 24 hours, pour out the supernatant, wash with anhydrous ethanol for 3 times, then wash with deionized water for 3-5 times, and freeze-dry to obtain modified zirconium oxide.

[0042] Example 1

[0043] A method for preparing an epoxy resin anti-collision, anti-corrosion and wear-resistant material comprises the following preparation steps:

[0044] Step 1: After heating and liquefying 25 g of epoxy resin, add 15 g of a mixture of xylene and n-butanol in a volume ratio of 1:2 and 2 g of dibutyl phthalate in sequence, and stir evenly;

[0045] Step 2: Add 4g of anticorrosive filler and 2.5g of wear-resistant filler, and stir to mix evenly;

[0046] Wherein, the preparation method of the anticorrosive filler is:

[0047] (1) 0.3 g and a specific surface area of ​​280 g / m 2 After mixing fumed silica, 2g of nickel nitrate hexahydrate and 1.2g of urea, add 50mL of 0.02mol / L nitric acid and stir until completely dissolved; under stirring, heat to 85°C and react for 7h; after the reaction is completed, cool to room temperature, then centrifuge, wash with water, and then place in a drying oven at 50°C to dry for 10h to obtain NiPS;

[0048] (2) Pour 0.5 g of NiPS and 18 g of zinc acetate dihydrate into 45 mL of deionized water and stir for 10 h to obtain solution A; pour 0.35 g of thiourea into 15 mL of deionized water and stir until the thiourea is completely dissolved to obtain solution B; mix solution A and solution B, heat to 150 °C, and react for 3.5 h; after the reaction is completed, cool naturally to room temperature, centrifuge, wash with water, and then place in a drying oven at 55 °C to dry for 10 h to obtain the anticorrosive filler;

[0049] The preparation method of wear-resistant filler is:

[0050] 1) Mix 1.8g of graphite powder and 2g of K 2 S 2 O 8 , 2g of P 2 O 5Pour into 10mL of concentrated sulfuric acid, heat to 75℃ in a water bath, and stir to react for 3h; then cool to room temperature, add 350mL of deionized water, let stand for 24h, pour out the supernatant, wash the precipitate with deionized water 3 times, and then dry in a drying oven at 60℃;

[0051] 2) Pour 120 mL of concentrated sulfuric acid into the pre-oxidized graphene and stir in an ice-water bath at 0 °C for 25 min; slowly add 12 g of potassium permanganate at room temperature and stir for 65 h; add 220 mL of deionized water and stir for 20 min; first add 650 mL of deionized water and then add 30% H 2 O 2 solution; centrifuge, pour off the supernatant, wash the precipitate three times with 10% by volume dilute hydrochloric acid and deionized water, and then dialyze to neutrality to obtain graphene oxide;

[0052] 3) After mixing 8 mL of graphene oxide and 4 mL of modified zirconium oxide, add 1.5 mL of N, N-dimethylformamide and perform ultrasonic treatment for 15 minutes; heat the oil bath to 65°C, react for 25 minutes, and then cool to room temperature; after standing for 24 hours, pour out the supernatant, wash the precipitate twice with anhydrous ethanol, then wash it three times with deionized water, and freeze-dry for 45 minutes to obtain the wear-resistant filler;

[0053] Step 3: Add 2 g of 2-ethyl acrylate, stir evenly, evacuate, mold, and cure in an oven at 50°C for 12 hours to obtain the epoxy resin anti-collision, anti-corrosion and wear-resistant material.

[0054] Example 2

[0055] A method for preparing an epoxy resin anti-collision, anti-corrosion and wear-resistant material comprises the following preparation steps:

[0056] Step 1: After heating and liquefying 28 g of epoxy resin, add 12 g of a mixture of xylene and n-butanol in a volume ratio of 1:2 and 1.6 g of dibutyl phthalate in sequence, and stir evenly;

[0057] Step 2: Add 3.2g of anticorrosive filler and 2.2g of wear-resistant filler, and stir to mix evenly;

[0058] Wherein, the preparation method of the anticorrosive filler is:

[0059] (2) 0.4 g and a specific surface area of ​​280 g / m 2After mixing fumed silica, 2.2 g of nickel nitrate hexahydrate and 1.3 g of urea, add 60 mL of 0.02 mol / L nitric acid and stir until completely dissolved; under stirring, heat to 88 ° C and react for 8 hours; after the reaction is completed, cool to room temperature, then centrifuge, wash with water, and then place in a drying oven at 55 ° C for 11 hours to obtain NiPS;

[0060] (2) Pour 0.65 g of NiPS and 20 g of zinc acetate dihydrate into 45 mL of deionized water and stir for 11 h to obtain solution A; pour 0.45 g of thiourea into 15 mL of deionized water and stir until the thiourea is completely dissolved to obtain solution B; mix solution A and solution B, heat to 160 ° C, and react for 3.8 h; after the reaction is completed, cool naturally to room temperature, centrifuge, wash with water, and then place in a drying oven at 60 ° C for 12 h to obtain the anticorrosive filler;

[0061] The preparation method of wear-resistant filler is:

[0062] 1) Mix 2.5g of graphite powder and 2.2g of K 2 S 2 O 8 , 2.3 g of P 2 O 5 Pour into 11mL of concentrated sulfuric acid, heat to 78℃ in a water bath, and stir to react for 4h; then cool to room temperature, add 400mL of deionized water, let stand for 24h, pour out the supernatant, wash the precipitate with deionized water 4 times, and then dry in a drying oven at 65℃;

[0063] 2) Pour 120 mL of concentrated sulfuric acid into the pre-oxidized graphene and stir for 30 min in an ice-water bath at 1 °C; slowly drop 15 g of potassium permanganate at room temperature and stir for 68 h; add 240 mL of deionized water and stir for 25 min; first add 700 mL of deionized water and then drop 30% H 2 O 2 solution; centrifuge, pour off the supernatant, wash the precipitate three times with 10% by volume dilute hydrochloric acid and deionized water, and then dialyze to neutrality to obtain graphene oxide;

[0064] 3) After mixing 12 mL of graphene oxide and 5 mL of modified zirconium oxide, add 2.5 mL of N, N-dimethylformamide and perform ultrasonic treatment for 20 minutes; heat the oil bath to 70°C, react for 30 minutes, and then cool to room temperature; after standing for 24 hours, pour out the supernatant, wash the precipitate with anhydrous ethanol for 3 times, then wash it with deionized water for 4 times, and freeze-dry for 55 minutes to obtain the wear-resistant filler;

[0065] Step 3: Add 1.7 g of 2-ethyl acrylate, stir evenly, evacuate, mold, and cure in an oven at 60° C. for 18 hours to obtain the epoxy resin anti-collision, anti-corrosion and wear-resistant material.

[0066] Example 3

[0067] A method for preparing an epoxy resin anti-collision, anti-corrosion and wear-resistant material comprises the following preparation steps:

[0068] Step 1: After liquefying 30 g of epoxy resin by heating, add 10 g of a mixture of xylene and n-butanol in a volume ratio of 1:2 and 1.5 g of dibutyl phthalate in sequence, and stir evenly;

[0069] Step 2: Add 2.5g of anticorrosive filler and 1.8g of wear-resistant filler, and stir to mix evenly;

[0070] Wherein, the preparation method of the anticorrosive filler is:

[0071] (3) 0.5 g and a specific surface area of ​​280 g / m 2 After mixing fumed silica, 2.4 g of nickel nitrate hexahydrate and 1.4 g of urea, add 565 mL of 0.02 mol / L nitric acid and stir until completely dissolved; under stirring, heat to 90°C and react for 8 hours; after the reaction is completed, cool to room temperature, then centrifuge, wash with water, and then place in a drying oven at 60°C to dry for 12 hours to obtain NiPS;

[0072] (2) Pour 0.75 g of NiPS and 22 g of zinc acetate dihydrate into 45 mL of deionized water and stir for 12 h to obtain solution A; pour 0.5 g of thiourea into 15 mL of deionized water and stir until the thiourea is completely dissolved to obtain solution B; mix solution A and solution B, heat to 170 °C, and react for 4 h; after the reaction is completed, cool naturally to room temperature, centrifuge, wash with water, and then place in a drying oven at 65 °C to dry for 14 h to obtain the anticorrosive filler;

[0073] The preparation method of wear-resistant filler is:

[0074] 1) Mix 3g of graphite powder and 2.5g of K 2 S 2 O 8 , 2.5g of P 2 O 5 Pour into 12mL of concentrated sulfuric acid, heat to 80℃ in a water bath, and stir to react for 4h; then cool to room temperature, add 450mL of deionized water, let stand for 24h, pour out the supernatant, wash the precipitate with deionized water 5 times, and then dry in a drying oven at 70℃;

[0075] 2) Pour 120 mL of concentrated sulfuric acid into the pre-oxidized graphene and stir for 35 min in an ice-water bath at 2 °C; slowly drop 18 g of potassium permanganate at room temperature and stir for 72 h; add 250 mL of deionized water and stir for 30 min; first add 750 mL of deionized water and then drop 30% H 2 O 2 solution; centrifuge, pour off the supernatant, wash the precipitate three times with 10% by volume dilute hydrochloric acid and deionized water, and then dialyze to neutrality to obtain graphene oxide;

[0076] 3) After mixing 15 mL of graphene oxide and 6 mL of modified zirconium oxide, add 4 mL of N, N-dimethylformamide and perform ultrasonic treatment for 25 minutes; heat the oil bath to 75°C, react for 40 minutes, and then cool to room temperature; after standing for 24 hours, pour out the supernatant, wash the precipitate with anhydrous ethanol for 3 times, then wash it with deionized water for 5 times, and freeze-dry for 65 minutes to obtain the wear-resistant filler;

[0077] Step 3: Add 1.5 g of 2-ethyl acrylate, stir evenly, evacuate, mold, and cure in an oven at 70°C for 24 hours to obtain the epoxy resin anti-collision, anti-corrosion and wear-resistant material.

[0078] Comparative Example 1

[0079] Compared with Example 1, the wear-resistant filler in Example 1 is replaced by graphite oxide and zirconium oxide; the rest remains unchanged.

[0080] Comparative Example 2

[0081] Compared with Example 1, the anti-corrosion filler in Example 1 is replaced by NiPS; the rest remains unchanged.

[0082] Tensile strength test: The test was carried out according to GB / T 2567-2021; the results are shown in Table 1.

[0083] Bending strength test: The test was carried out in accordance with GB / T 2567-2021; the results are shown in Table 1.

[0084] Impact strength test: The test was carried out in accordance with GB / T 2567-2021; the results are shown in Table 1.

[0085] Table 1

[0086]

[0087] Anticorrosion test: The test was conducted in accordance with GB / T 1771-2007; the epoxy resin material was coated on the surface of the copper plate, and cured at 160°C for 3h, 200°C for 3h, 230°C for 2h, and 260°C for 2h, and then placed in a salt spray test chamber for anticorrosion performance test at a temperature of 30°C for 720h; the results are shown in Table 2.

[0088] Table 2

[0089]

[0090] Friction coefficient test: The friction and wear test was carried out on a UMT-3MT friction tester with a loading force of 50N, a frequency of 3.3HZ, a stroke of 3mm, a pair Φ10mm, and a test time of 10min. The friction coefficient was directly obtained; the results are shown in Table 3.

[0091] Wear test: The prepared samples were weighed with a precision analytical balance before and after the friction test, and the weights were weighed 5 times each time. The average values ​​were taken to compare the average wear values. The results are shown in Table 3.

[0092] Table 3

[0093]

[0094] like Figure 1 As shown, the graphene sheets before oxidation are tightly overlapped, with a relatively regular shape and a relatively smooth surface; the graphene surface after oxidation has many wrinkles. This is due to the action of potassium permanganate and concentrated sulfuric acid, which makes the surface of graphene oxide have many oxygen-containing groups. These groups destroy the sp2 hybrid orbitals of carbon atoms in graphite and form a large number of sp3 hybrid orbitals. The sp3 hybrid orbitals cannot be in the same plane, thus forming a wrinkled structure. At the same time, the sheets of the wrinkled part of the graphene oxide are stacked into double layers or a few layers, and the number of layers is significantly less than that of graphite, which shows that the graphite has been completely oxidized and peeled off into graphene oxide.

[0095] like Figure 2 As shown, the modified zirconium oxide is more evenly dispersed on the surface of graphene oxide.

[0096] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0097] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An epoxy resin anti-collision, anti-corrosion and wear-resistant material, characterized in that: The invention comprises the following components in parts by weight: 2.5-4 parts of anticorrosive filler, 1.8-2.5 parts of wear-resistant filler, 25-30 parts of epoxy resin, 10-15 parts of diluent, 1.5-2 parts of defoaming agent and 1.5-2 parts of toughening agent; The diluent is a mixture of xylene and n-butanol in a volume ratio of 1:2; the defoamer is 2-ethyl acrylate; and the toughening agent is dibutyl phthalate; The preparation method of the anticorrosive filler is: S1. Pour 0.5-0.75 g of NiPS and 18-22 g of zinc acetate dihydrate into 45 mL of deionized water and stir for 10-12 h to obtain solution A. S2. Pour 0.35-0.5 g of thiourea into 15 mL of deionized water and stir until the thiourea is completely dissolved to obtain solution B; S3, after mixing solution A and solution B, raise the temperature to 150-170°C and react for 3.5-4h; S4, after the reaction is completed, cool naturally to room temperature, centrifuge, wash with water, and then place in a drying oven at 55-65°C to dry for 10-14h to obtain an anticorrosive filler; The preparation method of the NiPS is: S11, 0.3-0.5g and specific surface area of ​​280g / m 2 After mixing fumed silica, 2-2.4 g of nickel nitrate hexahydrate and 1.2-1.4 g of urea, add 50-65 mL of 0.02 mol / L nitric acid and stir until completely dissolved; S12, under stirring conditions, heating to 85-90°C and reacting for 7-8h; S13. After the reaction is completed, cool to room temperature, centrifuge, wash with water, and then place in a drying oven at 50-60°C to dry for 10-12 hours to obtain NiPS.

2. The epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 1, characterized in that: The wear-resistant filler is prepared by mixing graphene oxide and modified zirconium oxide.

3. The epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 1, characterized in that: The preparation method of the wear-resistant filler is: (1) After mixing 8-15 mL of graphene oxide and 4-6 mL of modified zirconium oxide, 1.5-4 mL of N,N-dimethylformamide was added and ultrasonic treatment was performed for 15-25 min; (2) Heat the oil bath to 65-75°C, react for 25-40 minutes, and then cool to room temperature; (3) After standing for 24 hours, pour off the supernatant, wash the precipitate with anhydrous ethanol for 2-3 times, then wash it with deionized water for 3-5 times, and freeze-dry it for 45-65 minutes to obtain the wear-resistant filler.

4. The epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 3, characterized in that: The preparation process of graphene oxide includes a pre-oxidation process and an oxidation process.

5. The epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 4, characterized in that: The pre-oxidation process of the graphene oxide is specifically as follows: 1.8-3g of graphite powder, 2-2.5g of K2S2O8, and 2-2.5g of P2O5 are poured into 10-12mL of concentrated sulfuric acid, heated to 75-80°C in a water bath, and stirred for reaction for 3-4h; then cooled to room temperature, 350-450mL of deionized water is added, and after standing for 24h, the supernatant is poured out, the precipitate is washed with deionized water for 3-5 times, and then placed in a drying oven at 60-70°C for drying.

6. The epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 5, characterized in that: The oxidation process of the graphene oxide is specifically as follows: Ⅰ. Pour 120 mL of concentrated sulfuric acid into the pre-oxidized graphene and stir in an ice water bath at 0-2°C for 25-35 min; Ⅱ. At room temperature, slowly add 12-18g of potassium permanganate and stir to react for 65-72h; III. Add 220-250 mL of deionized water and stir for 20-30 minutes; IV. First add 650-750mL of deionized water, then add 30% H2O2 solution; V. Centrifuge, discard the supernatant, wash the precipitate three times with 10% by volume dilute hydrochloric acid and deionized water, and then dialyze to neutral to obtain graphene oxide.

7. The epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 4, characterized in that: The preparation method of the modified zirconium oxide is: Add 1.5-4 g of 8-aminopyrene-1,3,6-trisulfonic acid trisodium salt and 10-15 g of nano zirconium oxide to 22-28 mL of anhydrous ethanol, stir evenly, and then ultrasonically disperse for 10-15 minutes; under stirring, heat the water bath to 45-50° C., and add deionized water; after natural precipitation for 24 hours, pour out the supernatant, wash with anhydrous ethanol for 3 times, then wash with deionized water for 3-5 times, and freeze-dry to obtain modified zirconium oxide.

8. A method for preparing the epoxy resin anti-collision, anti-corrosion and wear-resistant material according to claim 1, characterized in that: The method comprises the following preparation steps: Step 1: After the epoxy resin is heated and liquefied, a diluent and a toughening agent are added in sequence and stirred evenly; Step 2: Add anti-corrosion filler and wear-resistant filler, and stir to mix evenly; Step 3: Add defoaming agent, stir evenly, evacuate, mold, and cure in an oven at 50-70°C for 12-24h to obtain epoxy resin anti-collision, anti-corrosion and wear-resistant material.

Citation Information

Patent Citations

  • High-abrasion-proof epoxy resin composite material

    CN107759976A

  • Preparation method of graphene nanocomposite material

    CN102992304A

  • Graphene nanoparticle composite material and preparation method thereof

    CN107400396A